Sem and phylogenetic analysis of naturalized and cultivated Epidendrum in Hawaii - White, Ingelia P. (Universidad de Costa Rica, 2013)
Naturalized populations of Epidendrum L. are found on a rocky hillside in Nuuanu-Pali and Olomana in the Koolau Mountains of Oahu, Hawaii. Scanning electron micrographs were taken to observe polymorphism among the pollinia, petals, leaves, and root tips of two Epidendrum specimens (one naturalized specimen from Nuuanu-Pali and one cultivated specimen in the greenhouse). SEM images of pollen from the naturalized Epidendrum revealed a length of 830.31 μm and a width of 462.58 μm. Pollen length from the cultivated cultivar, by comparison, was 724.60 μm and the width 276.17 μm. Differing cell structures on the lower surface of the petals were also observed. Polyhedral concave cells with numerous fossae (pits) were seen on the naturalized cultivar and elongated flattened cells on the cultivated one. Transections of the leaf of the naturalized specimen were much thinner (546.33 μm) compared to the thickness of the cultivated cultivar leaf (1505.83 μm), which contained more spongy parenchyma cells. A thinner root tip (1094.19 μm) was seen in the naturalized cultivar, as opposed to 1636.34 μm in the cultivated specimen. To compare relationships between these two specimens along with ten other unknown Epidendrum cultivars, we sequenced the plastid trnL-F gene region and conducted parsimony analysis among the naturalized Epidendrum from Nuuanu-Pali At least six changes separated these specimens into two clades. Shorter and longer plastid simple sequence repeats (cpSSR) from the rps16-trnK region support separation of the five Epidendrum genotypes evaluated into these two groups, including a naturalized Epidendrum from Olomana.